Development of Environmental Awareness as a Pedagogical Strategy for the Preservation of Ecosystems - Castillo, Verenice Sánchez (Journal of Ecohumanism, 2024)
This article addresses a topic of current interest to the scientific community regarding ecosystem preservation as a pedagogical strategy that seeks to develop environmental awareness in individuals. In this regard, it addresses the importance of integrating environmental education into all academic processes and levels. It identifies environmental education as a key tool for promoting sustainability. This study was conducted using a bibliometric approach, consulting sources on the topic in high-impact databases between 2019 and 2023. Pedagogical strategies implemented to promote environmental awareness were analyzed. The consultation of sources highlighted the use of interdisciplinary approaches, innovative technologies, and the promotion of ecological values. These stand out as fundamental factors for ecosystem preservation. It was identified that environmental education includes, in addition to the transmission of knowledge, the formation of pro-environmental attitudes and behaviors. It can be affirmed that environmental awareness is developed systematically, contributing to transforming practices toward sustainability and the mitigation of environmental problems.